IMPLEMENTASI PRENATAL YOGA DAN SENAM HAMIL DALAM KELAS IBU HAMIL - Riska Susanti Pasaribu; Ridesman Ridesman; Deby Cintya Yun; Sarah Debora; Romaita Romaita; Diah Pitaloka Tarigan (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
Pregnancy is a period in which changes in a woman's biological condition are accompanied by psychological changes. During pregnancy, pregnant women experience physical and psychological changes that can cause discomfort such as dyspnea, insomnia, gingiviris and epulsion, frequent urination, pressure and discomfort in the perineum, back pain, constipation, varicose veins, fatigue, Braxton hicks contractions, leg cramps, ankle edema and mood swings and increased anxiety. The purpose of this study was to gain more knowledge and understand the implementation of prenatal yoga and pregnancy exercises in reducing physical complaints and labor readiness in pregnant women. This research is a quasi experimental research and the design used is a pre-test post-test research design with a control group design, the number of samples is 30 people, where the control group is 15 people and the intervention group is 15 people. The paired t test on the effect of prenatal yoga and pregnancy exercise in reducing physical complaints before and after delivery was p = 0.000, meaning p <0.05, stating that there is an effect of prenatal yoga and pregnancy exercise in reducing physical complaints. Preparation for childbirth in pregnant women. The independent t test found no difference in the effect of prenatal yoga and pregnancy exercise to reduce physical complaints during labor preparation with a value of p = 0.021. There was an effect of prenatal yoga and pregnancy exercise on the reduction of physical complaints of gloss p = 0,000, where the p value was <0.005, while the comparison test found no difference in the effect of prenatal yoga and pregnancy exercise to reduce physical complaints in preparation for labor with a value of p = 0.021.